2016
DOI: 10.1111/jfr3.12227
|View full text |Cite
|
Sign up to set email alerts
|

Local controversies of flood risk reduction measures in Germany. An explorative overview and recent insights

Abstract: In light of the flood event in June 2013, local disputes of flood risk reduction measures became a public concern in Germany, as it was argued that these controversies delayed the implementation of flood defence schemes and thus aggravated the flood impacts. However, actual knowledge about such disputes is generally quite limited. Therefore, this paper uses different empirical approaches to present first an explorative overview of such ongoing controversies with a focus on the measures under dispute and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 36 publications
(89 reference statements)
0
25
0
Order By: Relevance
“…On the one hand, protective measures are requested by parts of the affected population and enjoy strong acceptance in satisfying desires for safety. On the other hand they are rejected because of the side effects they have on the landscape and on nature, or because of particular usage interests (Otto et al 2016). Mobile systems often serve as a compromise solution for the protection of urban areas, but in the case of an event these require deployment forces that are then no longer available for other tasks.…”
Section: Flood Defense By Embankmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, protective measures are requested by parts of the affected population and enjoy strong acceptance in satisfying desires for safety. On the other hand they are rejected because of the side effects they have on the landscape and on nature, or because of particular usage interests (Otto et al 2016). Mobile systems often serve as a compromise solution for the protection of urban areas, but in the case of an event these require deployment forces that are then no longer available for other tasks.…”
Section: Flood Defense By Embankmentsmentioning
confidence: 99%
“…The public debate related to the flood in June 2013 also revealed that the planning and implementation of flood defense schemes form grounds for many disputes between authorities and the general public (Otto et al 2016). On the one hand, protective measures are requested by parts of the affected population and enjoy strong acceptance in satisfying desires for safety.…”
Section: Flood Defense By Embankmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although local stakeholder participation occurs for various aspects of FRM, including risk assessment (see DEFRA, ) and flood risk mapping (Meyer et al ., ), this paper is particularly interested in the way in which this responsibility is delegated and the participation formats that exist in order to improve flood defence schemes. Despite criticisms of flood defence approaches (Tobin, ; Etkin, ; Fordham, ), it remains favoured as a means of ensuring public safety and it is the area of FRM where most funding is spent (Otto et al ., ). Many decision‐making processes assume that structural defences decrease flood risk and assume that populations want them.…”
Section: Introductionmentioning
confidence: 97%
“…There is a particular emphasis on inclusive governance in which local stakeholders are encouraged to become involved in FRM-related decision-making processes, such as the planning and implementation of structural and nonstructural measures (DEFRA, 2011a, § 72 VwVfG). Much literature exists on the importance and benefits of involving local stakeholders in such decisions (Webler et al, 1995;Wisner, 1995;Few et al, 2007;Renn, 2008), but there is a lack of empirical studies which focus on the influence that such involvement can have on the final decision and the reduction of flood-related damage (Kuhlicke, 2014;Begg et al, 2015;Otto et al, 2016).…”
Section: Introductionmentioning
confidence: 99%